Fundamentals of optical fiber sensors - Fang, Zujie, 1942-; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley, 2012)
"This book describes the latest development in optical fiber devices, and their applications to sensor technology"--
Fundamentals of Optical Fibers -- Fiber Sensitivities and Fiber Devices -- Fiber Gratings and Related Devices -- Distributed Optical Fiber Sensors -- Fiber Sensors with Special Applications -- Extrinsic Fiber Fabryb6(BPerot Interferometer Sensor.s
Includes bibliographical references and index.
Print version record.
Keywords: Optical fiber detectors; Fiber optics; Optical fiber detectors; Fiber optics; TECHNOLOGY & ENGINEERING -- Electronics -- Semiconductors; TECHNOLOGY & ENGINEERING -- Sensors; Fiber optics; Optical fiber detectors; Electronic books